Juveniles of pink and chum salmon in the Iska River (Sakhalin Bay, Okhotsk Sea) in the fresh-water period - Albina N. Kanzeparova; Sergey F. Zolotukhin; Valery A. Balushkin (Известия ТИНРО, 2015)
Juveniles of pink and chum salmon are investigated in the Iska River flowing into the Okhotsk Sea. The pink juveniles begin their seaward migration in May, with the ice melting, the migration lasts about 40 days, approximately from May 20 to July 5. The seaward migration of chum juveniles begins in the same time but ends in 5-10 days later. The portion of pink salmon fry with the remains of yolk sac is 82-94 %; even in the end of their migration it is rather high, up to 76 %. This species juveniles begin to feed in the river, in particular in «dry» years, the portion of feeding fry increases with disappearance of the yolk sac up to 78 % (by the stomach fullness). Both pink and chum juveniles migrate at night only. Hydrological conditions influence on the timing of migration: it is close to normal dates in conditions of high water level and strong water flow but delayed in conditions of low water discharge (that’s why the portion of juveniles feeding in the river is higher in those years). Year-to-year dynamics of the juveniles and spawners abundance is traced for the 1951-2012. The pink salmon escapement to the Iska changed from 11.0 · 103 (in 2004) to 1344.4 · 103 (in 1958) ind., on average 280.0 · 103 ind. for even years and from 22.7 · 103 (in 1959) to 2005.8 · 103 (in 2007) ind., on average 372.9 · 103 ind. for odd years. The number of pink salmon downstream migrants changed from 0.8 · 106 (in 1954) to 40.9 · 106 (in 1964), on average 10.9 · 106 ind. for even years and from 1.0 · 106 (in 2005) to 41.8 · 106 (in 1957), on average 8.9 · 106 ind. for odd years.